Transformation Of Conflicts Based On Oral Tradition In West Kalimantan (From An Islamic Law Perspective) - Sardo Mangatur Pardamean Sibarani; Lomba Sultan; Abdul Wahid Haddade; Zarul Arifin (CBJIS: Cross-Border Journal of Islamic Studies, 2025)
West Kalimantan is a region rich in cultural diversity and traditions, including in terms of conflict resolution through local cultural approaches. One of these cultural treasures is the oral tradition, which serves as a medium for mitigating and resolving social conflicts that arise within the community. This study aims to examine the forms of conflict that occur in West Kalimantan, explore Islamic values regarding conflict resolution, and analyze the role of oral traditions as a means of conflict transformation from an Islamic legal perspective. This study uses a socio-legal approach with a descriptive qualitative method, where data is collected through literature review and interviews with traditional leaders, religious scholars, and local communities. The findings of this study indicate that conflicts in West Kalimantan are often related to social issues, cultural identity, and resource disputes, but they are successfully mitigated through oral traditions such as customary advice, pantun (traditional poetry), and customary deliberation, which are rich in values of justice, reconciliation, and brotherhood. These traditions align with the principles of Islamic law, which emphasize the importance of ishlah (peace), 'adalah (justice), and ta'ayush silmi (living together in peace). Thus, oral traditions not only function as cultural instruments but also as social legal mechanisms rooted in Islamic values in transforming conflicts into sustainable peace.